The Frequency of DNA Mismatch Repair Deficiency Is Very Low in Surgically Resected Lung Carcinoma - Yanagawa, Naoki; Yamada, Noriyuki; Sugimoto, Ryo; Osakabe, Mitsumasa; Uesugi, Noriyuki; Shiono, Satoshi; Endoh, Makoto; Ogata, Shin-ya; Saito, Hajime; Maemondo, Makoto; Sugai, Tamotsu (Frontiers in Oncology, 2021)
Introduction: DNA mismatch repair (MMR) deficiency leads to changes in the length of nucleotide repeat sequences of tumor DNA. In that situation, DNA replicational errors occur and accumulate during DNA replication. As a result, this mechanism frequently affects the coding regions of oncogenes and tumor suppressor genes and causes carcinogenesis. Recently, DNA MMR deficiency has been recognized as a predictive biomarker for immunotherapy. The aim of this study is to examine the frequency of DNA MMR deficiency and clinicopathological characteristics in surgically resected lung carcinoma (LC) and their correlation. Methods: A total of 1153 LCs were examined. Tissue microarrays were constructed. The status of MMR deficiency was evaluated by immunohistochemical analysis of MMR protein expression (hMLH1, hMSH2, hMSH6, and hPMS2). Microsatellite instability analysis, BRAF mutation, and MLH1 methylation analysis were performed for cases that showed MMR deficiency. Results: Only 2 of the 1153 cases (0.17%) showed a loss of hMLH1/hPMS2 protein expression. They also had high levels of microsatellite instability (MSI-H), had neither MLH1 promoter methylation nor BRAF mutation, and were male smokers. Histopathologically, one was a squamous cell carcinoma, and the other was combined small cell carcinoma with squamous cell carcinoma. Regarding PD-L1 protein expression, one had high expression, and the other had none. Conclusion: The frequency of MMR deficiency was very low in LC. However, our two cases were non-adenocarcinoma and differed from previous studies. Because of its very low frequency, MMR deficiency is not a useful biomarker to predict the effect of immune checkpoint inhibitors in LC.